Tthe theory of democracy and the relationship between Human Rights and popular sovereignty (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article discusses the Kantian component in the theory of deliberative democracy. It begins claiming that Kant not only incorporates individual rights but also the idea of popular sovereignty: This author values democracy; however, a system of principles has normative priority over the practice of collective self-determination. The text later shows that Habermas’s theory of deliberative democracy elaborates a Kantian justification. Thus, it does not reconstruct the balance between rights and democracy as it claims to do; it rather builds an argument similar to Kant’s.
Keywords: Kant; deliberative democracy; human rights; popular sovereignty